The Effect of Earnings Per Share, Return on Assets and Debt To Equity Ratio on Stock Prices In Mining Sector Companies Listed on The Indonesia Stock Exchange Period 2015-2019 - Dandy Prasetyo; Sunario Leonardo; Mila Yulia Herosian (Institute of Computer Science (IOCS), 2021)
This study aims to examine and analyze the effect of Earning Per Share, Return On Assets and Debt to Equity Ratio have an effect on stock prices in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is all mining sub-sector companies listed on the Indonesia Stock Exchange totaling 43 companies. The sample of this research is 11 companies with purposive sampling technique. The data analysis method used is multiple linear regression. The results of the f test where f count 15.364 > f table 2.79 with a significant level < 0.05 shows R Earning Per Share, Return On Assets and Debt to Equity Ratio simultaneously affect stock prices in mining sector companies listed on the Stock Exchange. Indonesian Securities for the 2015-2019 period. The results of the t-test research where the Earning Per Share and Debt to Equity Ratio variables do not have a significant effect on stock prices in mining sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period and only return on assets has an effect on stock prices in mining sector companies that listed on the Indonesia Stock Exchange for the 2015-2019 period. The results of the analysis of the coefficient of determination obtained the Adjusted R2 value of 0.473, meaning that the variation of the Earning Per Share, Return On Assets and Debt to Equity Ratio variables in explaining the Stock Price variable is 47.3%, while the remaining 52.7% is explained by another